Contemporary conditions for the development of chain hotels in Poland – introduction to the functioning of large tourist enterprises - Sala, Krzysztof; Szostak, Daniel (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2024)
Hospitality belongs to one of the world’s oldest and continuously functioning service sectors, the origin of which dates back to antiquity and the early Middle Ages. Like entities in other sectors, hospitality companies can function and often operate independently or within networks that trigger synergistic effects. The publication aims to present the current situation and forecasts for chain hospitality in Poland in the context of, among others, the military conflict in Ukraine and the post-pandemic period. Foreign and domestic hotel chains and operators active in the Polish tourism market were considered for the publication. The research hypothesis is as follows: In Poland, chain hospitality constantly develops despite unfavourable external factors affecting the domestic and incoming tourist traffic volume. These factors include the effects of the pandemic, economic recession, inflation and a significant influx of immigrants in connection with the war in Ukraine. The research methods include analysing the existing data and literary criticism. The article uses compact materials, statistical data and netography. The research results positively verify the thesis. The motives for choosing the publication theme were the author’s academic interests and the lack of literature in this area